2017
DOI: 10.1177/0266666917748985
|View full text |Cite
|
Sign up to set email alerts
|

Social media engagement in developing countries

Abstract: The progressiveness of social media in academic libraries is the gear to achieve the libraries’ objectives, particularly in term of facilities and services. In addition, academic librarians have been using social media as a key medium for marketing, communication, and collaboration. However, social media use in academic libraries, especially in developing countries, is not without controversy. Studies indicate that social networking by academic librarians is ineffective use of librarians’ time and effort. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…Use of these tools in the library is found to promote engagement, creativity and collaboration along with being useful in understanding users’ needs (Ramsey and Vecchione, 2014). Magoi et al (2017) showed that the publishing of literature on social media in academic libraries in developing countries continues to increase. They pointed to studies that emphasize the benefits of social media usefulness in academic libraries under five major themes: marketing and promotion of library services, professional/self-development, social interaction, media sharing and communication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Use of these tools in the library is found to promote engagement, creativity and collaboration along with being useful in understanding users’ needs (Ramsey and Vecchione, 2014). Magoi et al (2017) showed that the publishing of literature on social media in academic libraries in developing countries continues to increase. They pointed to studies that emphasize the benefits of social media usefulness in academic libraries under five major themes: marketing and promotion of library services, professional/self-development, social interaction, media sharing and communication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…She emphasises that for nurses, their professional and personal use of SM must take strict patient privacy laws into account to protect patient privacy. Magoi et al (2019) examined the use of SM in academic libraries in developing countries in Asia and Africa. Their study did not specifically pertain to SMRM but they reinforced that institutions like libraries must ensure they did not associate SMRM with a general avoidance of using SM, and to remember the potential benefits that could be gained from its effective use.…”
Section: Related Workmentioning
confidence: 99%
“…The authors have found out 1700 posts from 40 libraries SNS and interviewed 10 librarians. [18,19] surveyed the librarian's use of social media for professional development in Nigeria. He investigated some 1294 registered members of the Nigerian Library Association online forum and he has selected 297 respondents for this study.…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%